Analysis Of The Effect Of Implementing Work Culture And Leadership Style On Employee Performance Levels - Damara, Dio; Solehudin, Didin; Astuti, Dewi (Jurnal Scientia, 2024)
In this study, researchers were interested in researching with the aim of finding out how much influence the partial and simultaneous application of work culture and leadership style has on employee performance. This research uses a quantitative method approach with data collection techniques through distributing questionnaires and is supported by secondary data. The data analysis method used in this research is multiple linear regression analysis. The number of samples used was 50 respondents from employees of the Administration section of Radio Republik Indonesia (RRI) Jakarta, the sampling technique used was saturated sampling. The results of this research show that partially the Work Culture variable (X1) has an influence of tcount 4.056 >ttable 2,012 and Leadership Style (X2) is tcount 3,089 >ttable 2,012. Simultaneous test results obtained a count of 28,917 > F table 3.20. So simultaneously there is a positive and significant influence on the performance of (Y) Radio Republik Indonesia (RRI) Jakarta employees. The employee performance variable can be explained by work culture and leadership style variables of 55.2% and the remaining 44.8% is explained by other variables not tested in this research.